COMPOSITION EN ACIDES GRAS DU MUSCLE PECTORALIS MAJOR DE POULETS DE CHAIR NOURRIS PAR DES REGIMES SUPPLEMENTES A LA SPIRULINE (SPIRULINA SP) - Ait Saada, Djamal; Bouderoua, Kaddour; Mourot, Jacques; Selselet-Attou, Ghalem; Ait Chabane, Ouiza (Revue française de la recherche en viandes et produits carnés, 2012)
Meat fatty acids composition of broilers fed on diets supplemented by Spirulina Spirulina is an alga that attracts the attention of scientists nutritionists. Indeed, it’s an important source of nutrients in both human and animal nutrition. The objective of this study was to determine the effects of supplementation of broilers chicken’s diets by spirulina on the fatty acid composition of meat.Broilers chickens werefed for50 dayswithdietssupplementedbyspirulina. The fatty acids (FA) composition of meat show a significant amounts in polyunsaturated fatty acids (PUFAs) for spirulina group compared with the control group, (24.9 vs. 21, 5%). As such, the n-6 FA proportions in Spirulina group were in higher compared to spirulina group (22.4% vs. 19.5%-SP3-SP0, P <0.05). This difference of proportions between batches is mainly due to the presence of arachidonic acid.
Keywords: ACIDES GRAS; PECTORALIS MAJOR; REGIMES; SPIRULINA SP; POULET.